Ephemeral ecological speciation and the latitudinal biodiversity gradient. (23rd August 2016) - Cutter, Asher D.; Gray, Jeremy C.
Abstract : The richness of biodiversity in the tropics compared to high‐latitude parts of the world forms one of the most globally conspicuous patterns in biology, and yet few hypotheses aim to explain this phenomenon in terms of explicit microevolutionary mechanisms of speciation and extinction. We link population genetic processes of selection and adaptation to speciation and extinction by way of their interaction with environmental factors to drive global scale macroecological patterns. High‐latitude regions are both cradle and grave with respect to species diversification. In particular, we point to a conceptual equivalence of "environmental harshness" and "hard selection" as eco‐evolutionary drivers of local adaptation and ecological speciation. By describing how ecological speciation likely occurs more readily at high latitudes, with such nascent species especially prone to extinction by fusion, we derive the ephemeral ecological speciation hypothesis as an integrative mechanistic explanation for latitudinal gradients in species turnover and the net accumulation of biodiversity.